2022
DOI: 10.1186/s12864-022-08944-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural and developmental dynamics of Matrix associated regions in Drosophila melanogaster genome

Abstract: Background Eukaryotic genome is compartmentalized into structural and functional domains. One of the concepts of higher order organization of chromatin posits that the DNA is organized in constrained loops that behave as independent functional domains. Nuclear Matrix (NuMat), a ribo-proteinaceous nucleoskeleton, provides the structural basis for this organization. DNA sequences located at base of the loops are known as the Matrix Attachment Regions (MARs). NuMat relates to multiple nuclear proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Both methods of extraction uncover interactions that are the components of the same network, validating either the low-salt (LIS) or high-salt (NaCl) method as good enough to isolate S/MARs ( Linnemann et al, 2009 ). Another recent study found that interventions like heat stabilization strengthen the NuMat, where the basic molecular components remain unchanged ( Sureka et al, 2022 ).…”
Section: Genome-wide Distribution Of S/mars: Dynamic and Constitutive...mentioning
confidence: 99%
See 3 more Smart Citations
“…Both methods of extraction uncover interactions that are the components of the same network, validating either the low-salt (LIS) or high-salt (NaCl) method as good enough to isolate S/MARs ( Linnemann et al, 2009 ). Another recent study found that interventions like heat stabilization strengthen the NuMat, where the basic molecular components remain unchanged ( Sureka et al, 2022 ).…”
Section: Genome-wide Distribution Of S/mars: Dynamic and Constitutive...mentioning
confidence: 99%
“…Only two studies of genome-wide mapping of S/MAR investigate their dynamics during embryonic development or cellular differentiation ( Chunduri et al, 2022 ; Sureka et al, 2022 ). These studies, for the first time, uncovered that these attachment points can be categorized as dynamic or stable (Core-MARs) ( Figure 1 ).…”
Section: Genome-wide Distribution Of S/mars: Dynamic and Constitutive...mentioning
confidence: 99%
See 2 more Smart Citations
“…Collectively, these chromatin modifications influence its physical attributes, such as compaction and stiffness. Additionally, chromosomal loci can be physically constrained via tethering to external non-chromatin structures such as spindle microtubules, the nuclear lamina in interphase, matrix attachment regions (MARs), and scaffold attachment regions (SARs), or via internal tethering at the base of chromatin loops or by regions of entanglement [1][2][3][4][5]. Involved in a diversity of biological functions, tethering can be permanent and firm, as with the attachments at telomeres and centromeres in yeast [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%